Modification of Seed Oil Composition in Arabidopsis by Artificial microRNA-Mediated Gene Silencing - Belide, Srinivas; Petrie, James R.; Shrestha, Pushkar; Singh, Surinder P. (Frontiers in Plant Science, 2012)
Various post transcriptional gene silencing (PTGS) strategies have been developed and exploited to study gene function or engineer disease resistance. The recently-developed artificial microRNA (amiRNA) strategy is an alternative method of effectively silencing target genes. The ∆12-desaturase (FAD2), Fatty acid elongase (FAE1) and Fatty acyl-ACP thioesterase B (FATB) were targeted with amiR159b-based constructs in Arabidopsis thaliana to evaluate changes in oil composition when expressed with the seed-specific Brassica napus truncated napin (FP1) promoter. Fatty acid profiles from transgenic homozygous seeds reveal that the targeted genes were silenced. The down-regulation of the AtFAD-2 gene substantially increased oleic acid from the normal levels of 15% to as high as 63.3% and reduced total PUFA content (18:2∆9,12+18:3∆9,12,15) from 44.8% to 4.7%. ∆12-desaturase activity was reduced to levels as low as those in the null fad-2-1 and fad-2-2 mutants. Silencing of the FAE-1 gene resulted in the reduction of eicosenoic acid (20:1∆11) to 1.9+1.0% from 15% and silencing of FATB resulted in the reduction of palmitic acid (16:0) to 4.4+0.5% from 8.0%. Reduction in FATB activity is comparable with a FATB-knock out mutant. These results demonstrate for the first time amiR159b constructs targeted against three endogenous seed-expressed genes are clearly able to down regulate and generate genotypic changes that are inherited stably over three generations.